Right to difference and pluriversality of indigenous peoples: Kanhgág time-space (Tempo e Argumento, 2023)
It is known that indigenous peoples in Brazil constitute various populations, however, what does this represent for the subject History? This article addresses this issue through the right to difference and pluriversality related to the irrevocable past. In this way, it is possible to think through indigenous histories based on philosophies involved in these processes. To do this, it is worth bringing the example of the ethnic group Kanhgág by means of its historicity.
Keywords: law; difference; indegenous; historicities; hanhgág